POTENSI DAN PERAN BAITUL MAL WAT TAMWIL TERHADAP PENGEMANGAN USAHA KECIL DI KOTA JAMBI - Elmiliyani Wahyuni S (Jurnal Akuntansi, 2016)
This research will explore the potential and role ofBMT in Jambi and to find out the influence of the roleof BMT in terms of granting financing towards thedevelopment of small businesses in Jambi, with acase study on 4 BMT, namely Al-ishlah, BMTKossuma (Salimah), BMT Bina Insan Sejahtera (BIS)and BMT Mayitoh. This research uses a quantitativeapproach with the objective to examine therelationship between the variables examinedthrough hypothesis testing. To know the influence ofthe role of BMT in terms of granting financingtowards the development of small businesses inJambi used linear regression equation of simplemodels. The results showed that the potential smallbusiness development towards the BMT in Jambi is inthe category either, for the application of the role ofBMT towards the development of small businesses inJambi is in the category is good enough, and therewas a significant influence between the role of BMTin terms of granting financing towards thedevelopment of small businesses in Jambi.